Pattern of Handling Rejuvenation of Slum Areas in the Bantan Area in Bantan Village, West Siantar District, Pematang Siantar City - Edy Saputra; Abdi Sugiarto; Cut Nuraini (Yayasan Sinergi Multidimensi Kreatif, 2025)
This study aims to examine the Improvement of the Quality of Slum Areas with the Pattern of Handling theRejuvenation of Slum Areas in the Bantan Area in Bantan Village, West Siantar District, Pematang Siantar City.The method used in this study can be in the form of qualitative descriptive research with a case study approach.This research was conducted in the Bantan Area, Bantan Village, West Siantar District, Pematang Siantar City.The data obtained will be analyzed using a qualitative descriptive analysis method, where data collected throughinterviews, observations, and documents are analyzed to provide a clear description of the condition of slumsand the pattern of handling rejuvenation applied in the Bantan Area. Results of the Initial Conditions of Concernstudy The Bantan area before rejuvenation faced various challenges, including poor infrastructure, highpopulation density, and low access to basic services such as clean water and sanitation. Implementation ofIntegrated Handling Patterns The rejuvenation program carried out adopts an integrated handling pattern bypaying attention to physical, social, and environmental aspects. Positive Impact on Quality of Life The results ofthe implementation of rejuvenation show an improvement in the quality of life of the community. IncreasedEnvironmental Awareness Through active involvement in rejuvenation, the community shows increasedawareness of the importance of maintaining cleanliness and environmental sustainability.